NEED ANALYSIS IN ENGLISH FOR YOUNG LEARNERS’ ASSESSMENT - Fajar Wirawan; Loly Novita; Silviana Masran; Widi Syaftinentias (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study examines the assessment needs of English for Young Learners (EYL) in Indonesian primary schools using a qualitative research design. The research aims to identify current assessment practices, challenges faced by teachers, and what is needed to improve assessment quality for young learners. Data were collected through classroom observations, semi-structured interviews with three EYL teachers, and analysis of lesson plans, worksheets, and assessment reports from three different schools. The findings indicate that assessment practices are still dominated by traditional written tasks, such as worksheets and quizzes, which account for most classroom assessments. These methods are not fully appropriate for young learners, who require interactive, play-based, and performance-based activities. Observations also show limited use of speaking tasks, games, and authentic assessments. Teachers provide minimal feedback, and none use rubrics or checklists to guide scoring Interviews reveal that teachers have limited assessment literacy due to a lack of training in child language evaluation. Time limitations, class size, and curriculum demands also hinder the implementation of developmentally appropriate assessment. The study concludes that teachers need practical, child-friendly assessment tools—such as simple rubrics, checklists, and performance task templates—and professional development in authentic and age-appropriate assessment strategies.